Anti-glare gradient glass, preparation method thereof and electronic device

CN118269005BActive Publication Date: 2026-10-09BYD CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311260065.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2026-10-09
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

[0005]本发明的目的是提供一种防眩光渐变玻璃及其制备方法和电子设备,以解决渐变玻璃雾度渐变不连续,难以满足外观丝滑要求的问题,以及制备工艺流程复杂,成本较高的问题

Benefits of technology

[0020] Through the above technical solutions, the gradient glass obtained by this invention has a good gradient effect, continuous haze gradient, and natural transition area. This invention also provides a method for preparing the aforementioned gradient glass, which involves first spraying the entire surface of the glass body with hard sand to increase overall haze, and then performing gradient-type spraying with a coated sand polishing to reduce haze, thereby obtaining glass with a gradient effect. The preparation process of the gradient glass of this invention is fluorine-free and environmentally friendly, which is beneficial to environmental development. The preparation method is simple and efficient, which helps to reduce the manufacturing cost of gradient glass, and it is suitable for mass production with a high yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118269005B_ABST
    Figure CN118269005B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of anti-dazzle gradient glass and its preparation method and electronic equipment, the difference between the two points of any 3 millimeters apart on the first surface of the gradient glass is in the range of 0.01-5% between the haze maximum value on the first surface is any value between 70-90%, and the minimum value of the haze on the first surface is any value between 5-15%.The preparation method of the gradient glass includes: S1, the surface of glass body is treated with first sandblasting using hard sand, to obtain first glass body;S2, the first glass body is treated with second sandblasting using film-coated sand, to obtain second glass body;The first sandblasting treatment is whole surface type sandblasting;The second sandblasting treatment is gradient type sandblasting.The gradient glass obtained by the present application has good gradient effect and natural transition area.The preparation process of the gradient glass of the present application is fluorine-free and environmentally friendly, which is conducive to environmental development, and the preparation method is simple and efficient, which is conducive to reducing the manufacturing cost of gradient glass, and is suitable for mass production with high yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of glass technology, specifically to an anti-glare gradient glass, its preparation method, and an electronic device thereof. Background Technology

[0002] With the rapid development of electronic devices, glass housings with a variety of decorative effects have been developed, such as gradient glass. Currently, there are various methods for preparing gradient glass, such as the process of exposure, development, masking, and then frosting; the process of frosting followed by hydrofluoric acid immersion or Czochralski chemical etching; and the process of adding haze to a material after low-haze frosting.

[0003] CN107009275A discloses a method for processing frosted glass with a gradient effect. The method includes the steps of: applying a protective film to the side of a glass substrate that does not require frosting; performing a gradient sandblasting treatment on the glass substrate after the protective film is applied; and cleaning the sandblasted glass substrate to obtain frosted glass with a gradient effect.

[0004] However, the haze gradient of gradient glass is currently discontinuous, making it difficult to meet the requirement of a smooth appearance, and the manufacturing process is complex and costly. Summary of the Invention

[0005] The purpose of this invention is to provide an anti-glare gradient glass, its preparation method, and an electronic device, in order to solve the problems of discontinuous haze gradient of gradient glass, which makes it difficult to meet the requirements of a smooth appearance, as well as the problems of complex preparation process and high cost.

[0006] To achieve the above objectives, the first aspect of the present invention provides an anti-glare gradient glass, the anti-glare gradient glass comprising a glass body having a first surface, wherein the haze difference between any two points 3 mm apart on the first surface is in the range of 0.01-5%, preferably in the range of 0.1-1.5%; the maximum haze value on the first surface is any value between 70-90%, and the minimum haze value on the first surface is any value between 5-15%.

[0007] Optionally, the haze difference between any two points 3 mm apart on the first surface is in the range of 0.1-1.5%; the light transmittance at any position on the first surface is greater than 85%.

[0008] Optionally, the maximum surface roughness Ra on the first surface is 1.6-2.0 μm, and the minimum surface roughness Ra on the first surface is 0.1-0.5 μm.

[0009] A second aspect of the present invention provides a method for preparing anti-glare gradient glass, the method comprising:

[0010] S1. The surface of the glass body is subjected to a first sandblasting treatment using hard sand to obtain a first glass body;

[0011] S2. The first glass body is subjected to a second sandblasting treatment using coated sand to obtain a second glass body;

[0012] The first sandblasting treatment is full-surface sandblasting; the second sandblasting treatment is gradient sandblasting.

[0013] Optionally, the first sandblasting process includes: controlling the spray gun to continuously spray the hard sand or a first spray material containing the hard sand and water from one end of the glass body to the other end of the glass body at a constant first predetermined speed and a first predetermined spraying distance to form the first glass body.

[0014] Optionally, the first predetermined speed is 1-100 mm / s, the first predetermined spraying distance is 40-1000 mm, and the particle size of the hard sand is 100 mesh-1000 mesh.

[0015] Optionally, the second sandblasting process includes: the spraying direction of the spray gun is set at an angle relative to the plane where the first glass body is located, and the spray gun is controlled to continuously spray the coated sand or a second spray material containing the coated sand and water from one end of the first glass body to the other end of the first glass body according to a second predetermined spraying distance and a gradually changing second predetermined speed, so as to form the second glass body.

[0016] Optionally, the second predetermined spray distance is 100-600mm, the angle between the spray direction of the spray gun and the plane where the first glass body is located is 15-90°, the pressure of spraying the coated sand is 0.1-0.8MPa, and the second predetermined speed is adjusted to a gradually changing second predetermined speed by gradually increasing or decreasing the moving speed of the spray gun; the gradually increasing or decreasing moving speed of the spray gun is 1-100mm / s.

[0017] Optionally, the coated sand comprises hard particles and a polymer film wrapped around the hard particles; the hard particles are at least one of white fused alumina, brown fused alumina, iron sand and zircon sand; the polymer film is at least one of polyurethane film, epoxy resin film and phenolic resin film; the weight ratio between the hard particles and the polymer film is 0.5-1.5:1.

[0018] Optionally, the method further includes: subjecting the second glass body to alkaline etching treatment; wherein the alkaline substance used for alkaline etching treatment is at least one of sodium hydroxide and potassium hydroxide, the concentration of the alkaline substance is 30-50%, the temperature of alkaline etching is 110-140℃, and the etching time is 40-60 min.

[0019] A third aspect of the present invention provides an electronic device comprising the gradient glass provided in the second aspect of the present invention.

[0020] Through the above technical solutions, the gradient glass obtained by this invention has a good gradient effect, continuous haze gradient, and natural transition area. This invention also provides a method for preparing the aforementioned gradient glass, which involves first spraying the entire surface of the glass body with hard sand to increase overall haze, and then performing gradient-type spraying with a coated sand polishing to reduce haze, thereby obtaining glass with a gradient effect. The preparation process of the gradient glass of this invention is fluorine-free and environmentally friendly, which is beneficial to environmental development. The preparation method is simple and efficient, which helps to reduce the manufacturing cost of gradient glass, and it is suitable for mass production with a high yield.

[0021] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description

[0022] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings:

[0023] Figure 1 This is a schematic diagram of the gradient glass in Embodiment 1 of the present invention.

[0024] Figure 2 This is an electron microscope image of the gradient glass in Embodiment 1 of the present invention.

[0025] Figure 3 These are the haze variation curves along the length direction of the gradient glass in Examples 1-3 and Comparative Examples 1-3. Detailed Implementation

[0026] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0027] The first aspect of the present invention provides an anti-glare gradient glass, the anti-glare gradient glass comprising a glass body having a first surface, wherein the haze difference between any two points 3 mm apart on the first surface is in the range of 0.01-5%, preferably in the range of 0.1-1.5%; the maximum haze value on the first surface is any value between 70-90%, and the minimum haze value on the first surface is any value between 5-15%; within this haze range, anti-glare glass substrates with different haze can be formed.

[0028] According to the present invention, optionally, the maximum surface roughness Ra on the first surface is 1.6-2.0 μm, and the minimum surface roughness Ra on the first surface is 0.1-0.5 μm; within this roughness range, a fine texture of varying degrees can be formed, and it is not easy to get sweaty when touched, thus having an anti-slip effect.

[0029] According to the present invention, optionally, the light transmittance at any position on the first surface is greater than 85%.

[0030] According to the present invention, optionally, the first surface has at least one gradient region, wherein the haze in the gradient region increases along at least one preset direction. The preset direction can be any direction, such as the length direction or the width direction of the glass body. In areas with high haze, diffuse reflection is stronger and the anti-glare effect is better, but the transmittance is relatively lower; in areas with low haze, diffuse reflection is relatively weaker, but the transmittance is higher.

[0031] A second aspect of the present invention provides a method for preparing anti-glare gradient glass, the method comprising:

[0032] S1. The surface of the glass body is subjected to a first sandblasting treatment using hard sand to obtain a first glass body;

[0033] S2. The first glass body is subjected to a second sandblasting treatment using coated sand to obtain a second glass body;

[0034] The first sandblasting treatment is full-surface sandblasting; the second sandblasting treatment is gradient sandblasting.

[0035] In this invention, the glass body is first subjected to a full-surface hard sandblasting to increase the overall haze to over 90%, giving the surface a certain roughness and thus high haze. Then, a gradient sandblasting process is applied for polishing to reduce the haze, forming a gradient haze surface with varying degrees of depth, resulting in a glass with a gradient effect. The preparation method of this invention is simple, efficient, low-cost, and environmentally friendly, suitable for mass production, and produces gradient glass with excellent gradient effects, continuous haze transitions, and natural transition areas.

[0036] According to the present invention, the specific type of glass body is not particularly limited and can be any known type of glass, such as silicate glass, phosphate glass, and borate glass, etc., and can be flexibly selected according to the actual application.

[0037] According to the present invention, optionally, the sandblasting method of the present invention can be dry sandblasting or wet sandblasting. For example, in dry sandblasting, the operation of the first sandblasting process includes: controlling the spray gun to continuously spray the hard sand from one end of the glass body to the other end of the glass body at a constant first predetermined speed and a first predetermined spraying distance to form the first glass body. In wet sandblasting, the operation of the first sandblasting process includes: controlling the spray gun to continuously spray a first spray material formed by the hard sand and water from one end of the glass body to the other end of the glass body at a constant first predetermined speed and a first predetermined spraying distance to form the first glass body.

[0038] According to the present invention, optionally, the first predetermined speed is 1-100 mm / s and the first predetermined spraying distance is 40-600 mm; within this predetermined speed and predetermined distance range, uniform sandblasting particles can be formed on the entire surface, resulting in high fog level and good anti-glare effect.

[0039] According to the present invention, optionally, the particle size of the hard sand is 100-1000 mesh. The hard sand includes at least one selected from white corundum, brown corundum, quartz sand, iron sand, corundum, and zirconium sand.

[0040] According to the present invention, optionally, the second sandblasting process includes: the spraying direction of the spray gun is set at an angle relative to the plane where the first glass body is located, and the spray gun is controlled to continuously spray the coated sand or a second spray material containing the coated sand and water from one end of the first glass body to the other end of the first glass body according to a second predetermined spraying distance and a gradually changing second predetermined speed, so as to form the second glass body.

[0041] According to the present invention, optionally, the second predetermined spray distance is 100-600mm, the angle between the spray direction of the spray gun and the plane where the first glass body is located is 15-90°, the pressure of spraying the coated sand is 0.1-0.8MPa, and the second predetermined speed is adjusted to a gradually changing second predetermined speed by gradually increasing or decreasing the moving speed of the spray gun; the gradually increasing or decreasing moving speed of the spray gun is 1-100mm / s. Within this angle and the range of gradually increasing or decreasing moving speed of the spray gun, a gradual transition sandblasting effect can be formed, with uniform sandblasting effect, no splicing marks, and a smooth and delicate feel. The angle between the spray direction of the spray gun and the plane where the first glass body is located, the second predetermined spray distance, and the gradually increasing or decreasing moving speed of the spray gun can be selected according to the haze of the actual product.

[0042] According to the present invention, optionally, the coated abrasive comprises hard particles and a polymer film coated on the hard particles; the hard particles are at least one selected from white fused alumina, brown fused alumina, quartz sand, iron sand, corundum, and zirconium sand; the polymer film is at least one selected from polyurethane film, epoxy resin film, and phenolic resin film; the weight ratio between the hard particles and the polymer film is 0.5-1.5:1. The coated abrasive can polish and grind the glass surface, and after gradient jet polishing with the coated abrasive, a gradient anti-glare effect is formed.

[0043] According to the present invention, optionally, the method further includes: subjecting the second glass body to alkaline etching treatment; wherein the alkaline substance used in the alkaline etching treatment is at least one of sodium hydroxide and potassium hydroxide, the concentration of the alkaline substance is 30-50%, the alkaline etching temperature is 110-140℃, and the etching time is 40-60 min. The purpose of using chemical etching is to remove microcracks on the glass surface, to etch the particles of the uneven structure on the glass surface into a smooth and rounded shape, to remove burrs, and to form diffuse reflection, thus creating an anti-glare effect; at the same time, it improves the performance of the glass.

[0044] A third aspect of this invention provides an electronic device comprising the gradient glass provided in the second aspect of this invention. This gradient glass, while possessing a gradient effect, can meet the usage requirements of electronic devices, particularly the requirements for cover plates, greatly expanding the application range of gradient glass. For example, when applying color decoration to the back of a mobile phone cover, the gradient glass's overall haze and other differences can create a visually appealing gradient transition.

[0045] The present invention will be further illustrated by the following examples, but the present invention is not limited thereto.

[0046] In the embodiments and comparative examples of this invention, the surface roughness was measured using a surface roughness measuring instrument, model: Mittutovosj-411, and the haze and transmittance were measured using a transmission haze meter 4725.

[0047] Example 1

[0048] This embodiment illustrates the preparation of anti-glare gradient glass and its preparation method, which includes:

[0049] S1. The surface of the silicate glass body is subjected to a full-surface first sandblasting treatment. The spray gun is controlled to continuously spray white corundum (particle size of 150 mesh) from one end of the glass body to the other end of the glass body at a constant first predetermined speed of 10 mm / s and a first predetermined spraying distance of 100 mm, forming a first glass body with an anti-glare and high haze surface.

[0050] S2. Perform a gradient second sandblasting treatment on the first glass body. The spray direction of the spray gun has a 45° angle with the plane where the first glass body is located. The spraying distance is 250mm, with a constant sandblasting pressure of 0.25MPa, an initial speed of 10mm / s, and the spray gun's moving speed is gradually increased to 80mm / s. The spraying begins from one end of the first glass body (…). Figure 1 (Middle B end) towards the other end of the first glass body ( Figure 1 The coated sand is continuously sprayed from end A to form a second glass body; the coated sand is white fused alumina wrapped with a polyurethane film, and the weight ratio between white fused alumina and polyurethane film is 1.5:1.

[0051] S3. The second glass body is subjected to alkaline etching treatment using 50% sodium hydroxide at a high temperature of 120°C for 50 minutes to obtain gradient glass.

[0052] The haze difference between any two points 3 mm apart on the first surface of the gradient glass is within the range of 1-1.5%. The maximum haze value at end A of the first surface is 72.3%, and the maximum roughness Ra is 1.723 μm. The minimum haze value at end B is 12.8%, and the minimum roughness Ra is 0.324 μm. The transmittance is greater than 85% in both cases, as shown in Table 1. In this embodiment, the glass body is 160 mm long. The haze is measured at 3 mm intervals between two points on the first surface of the glass body from end A to end B. The haze variation curve of the gradient glass along the length direction is shown in Table 1. Figure 3 As shown.

[0053] Example 2

[0054] This embodiment illustrates the preparation of anti-glare gradient glass and its preparation method, which includes:

[0055] S1. Perform a full-surface first sandblasting treatment on the surface of the silicate glass body. Control the spray gun to continuously spray white corundum (particle size of 100 mesh) from one end of the glass body to the other end of the glass body at a first predetermined speed of 50 mm / s and a first predetermined spraying distance of 300 mm to form a first glass body with AG high haze surface.

[0056] S2. Perform a gradient second sandblasting treatment on the first glass body. The spray direction of the spray gun has a 65° angle with the plane where the first glass body is located. The spraying distance is 300mm, with a constant sandblasting pressure of 0.35MPa, an initial speed of 80mm / s, and the spray gun's moving speed is gradually reduced to 15mm / s. The spraying begins from one end of the first glass body (…). Figure 1 (End A) towards the other end of the first glass body ( Figure 1 The coated sand is continuously sprayed from the middle B end to form a second glass body; the coated sand is white fused alumina wrapped with a polyurethane film, and the weight ratio between white fused alumina and polyurethane film is 1:1.

[0057] S3. The second glass body is subjected to alkaline etching treatment using 50% sodium hydroxide at a high temperature of 120°C for 50 minutes to obtain gradient glass.

[0058] The haze difference between any two points 3 mm apart on the first surface of the gradient glass is in the range of 1-1.4%. The maximum haze value at end A of the first surface is 78.1%, and the maximum roughness Ra is 1.834 μm. The minimum haze value at end B is 12.9%, and the minimum roughness Ra is 0.365 μm. The transmittance is greater than 85% in both cases, as shown in Table 1. In this embodiment, the length of the glass body is 160 mm. The haze is measured at two points 3 mm apart on the first surface of the glass body from end A to end B. The haze variation curve of the gradient glass along the length direction is shown in Table 1. Figure 3 As shown.

[0059] Example 3

[0060] This embodiment illustrates the preparation of anti-glare gradient glass and its preparation method, which includes:

[0061] S1. The surface of the silicate glass body is subjected to a full-surface first sandblasting treatment. The spray gun is controlled to continuously spray white corundum (particle size of 150 mesh) from one end of the glass body to the other end of the glass body at a constant first predetermined speed of 10 mm / s and a first predetermined spraying distance of 100 mm, forming a first glass body with an anti-glare and high haze surface.

[0062] S2. Perform a gradient second sandblasting treatment on the first glass body. The spray direction of the spray gun has a 45° angle with the plane where the first glass body is located. The spraying distance is 250mm, with a constant sandblasting pressure of 0.25MPa, an initial speed of 10mm / s, and the spray gun's moving speed is gradually increased to 80mm / s. The spraying begins from one end of the first glass body (…). Figure 1 (Middle B end) towards the other end of the first glass body ( Figure 1 The coated sand, which is white fused alumina wrapped with a polyurethane film, is continuously sprayed from end A in the middle. The weight ratio between the white fused alumina and the polyurethane film is 1.5:1 to form a second glass body and obtain gradient glass.

[0063] The haze difference between any two points 3 mm apart on the first surface of the gradient glass is in the range of 1-1.8%. The maximum haze value at end A of the first surface is 99.9%, and the maximum roughness Ra is 1.897 μm. The minimum haze value at end B is 10.6%, and the minimum roughness Ra is 0.384 μm. The transmittance is greater than 85% in both cases, as shown in Table 1. In this embodiment, the length of the glass body is 160 mm. The haze is measured at 3 mm intervals between two points on the first surface of the glass body from end A to end B. The haze variation curve of the gradient glass along the length direction is shown in Table 1. Figure 3 As shown.

[0064] Comparative Example 1

[0065] The method for preparing anti-glare gradient glass in this comparative example is the same as in Example 1, except that the coated sand in the second sandblasting process is replaced with hard white corundum, i.e., no polymer film is wrapped around it, thus obtaining gradient glass.

[0066] The haze difference between any two points 3 mm apart on the first surface of the gradient glass is within the range of 0.05-0.5%. The maximum haze at end B of the first surface is 80.8%, the maximum roughness Ra is 1.821 μm, and the transmittance is 83.5%. The minimum haze at end A is 72.7%, the minimum roughness Ra is 1.725 μm, and the transmittance is 84.4%, as shown in Table 1. The length of the glass body in this comparative example is 160 mm. The haze was measured at 3 mm intervals between two points on the first surface of the glass body from end A to end B. The haze variation curve of the gradient glass along the length direction is shown in Table 1. Figure 3 As shown.

[0067] Comparative Example 2

[0068] The method for preparing anti-glare gradient glass in this comparative example is the same as in Example 1, except that: instead of performing the first sandblasting treatment, the surface of the silicate glass body is directly subjected to a gradient second sandblasting treatment, and the coating sand in the second sandblasting treatment is replaced with hard white corundum sand, thereby obtaining gradient glass.

[0069] The haze difference between any two points 3 mm apart on the first surface of the gradient glass is in the range of 0.5-2.5%. The maximum haze at end B of the first surface is 82.3%, the maximum roughness Ra is 1.372 μm, and the transmittance is 84.1%. The minimum haze at end A is 0.2%, the minimum roughness Ra is 0.105 μm, and the transmittance is 93.8%, as shown in Table 1. The length of the glass body in this comparative example is 160 mm. The haze was measured at 3 mm intervals between two points on the first surface of the glass body from end A to end B. The haze variation curve of the gradient glass along the length direction is shown in Table 1. Figure 3 As shown.

[0070] Comparative Example 3

[0071] The method for preparing anti-glare gradient glass in this comparative example includes the following steps:

[0072] S1. Prepare the frosting solution. The main components of the frosting solution are ammonium fluoride, ammonium hydrogen fluoride, sodium fluoride, starch, barium sulfate, etc. Immerse the silicate glass body in the frosting solution for about 2 minutes to perform frosting treatment and form the first glass body.

[0073] S2. Perform a gradient second sandblasting treatment on the first glass body. The spray direction of the spray gun has a 45° angle with the plane where the first glass body is located. The spraying distance is 250mm, with a constant sandblasting pressure of 0.25MPa, an initial speed of 10mm / s, and the spray gun's moving speed is gradually increased to 80mm / s. The spraying begins from one end of the first glass body (…). Figure 1 (Middle B end) towards the other end of the first glass body ( Figure 1 The hardened alumina is continuously sprayed from end A to form a second glassy body;

[0074] S3. The second glass body is immersed in hydrofluoric acid solution for chemical polishing to obtain gradient glass.

[0075] The haze difference between any two points 3 mm apart on the first surface of the gradient glass is in the range of 0.08-0.6%. The maximum haze at end B of the first surface is 80.5%, the maximum roughness Ra is 1.802 μm, and the transmittance is 86.6%; the minimum haze at end A is 71.8%, the minimum roughness Ra is 0.698 μm, and the transmittance is 87.8%, as shown in Table 1. The length of the glass body in this comparative example is 160 mm. The haze was measured at 3 mm intervals between two points on the first surface of the glass body from end A to end B. The haze variation curve of the gradient glass along the length direction is shown in Table 1. Figure 3 As shown.

[0076] Table 1

[0077]

[0078] In summary, Embodiments 1 and 2 of this invention first perform full-surface sandblasting on the glass body to increase overall haze, and then perform gradient sandblasting and polishing to reduce haze, forming a gradient haze surface with layers, thereby obtaining glass with a gradient effect. Embodiment 3, without alkaline etching treatment, results in a gradient glass surface that is not smooth enough, and the glass transmittance is relatively low. In Comparative Example 1, replacing the coated sand with hard sand and not covering the polishing material results in haze superimposed on the first glass body with a high haze surface, failing to achieve the effect of reducing haze and forming a gradient haze surface with layers, as described in this invention, through sandblasting and polishing, thus obtaining glass with a gradient effect. In Comparative Example 2, directly using hard sand white corundum for gradient sandblasting on the glass body results in a more abrupt and less smooth haze change in the gradient glass, with an unnatural transition zone. In Comparative Example 3, the glass body was first frosted to achieve a low-haze zone, then sandblasted to create a high-haze layer on top of the low-haze layer to achieve a gradient effect. Finally, chemical polishing was performed. The resulting gradient glass exhibited discontinuous haze changes, and the polishing solution contained hydrofluoric acid, which is environmentally unfriendly. Therefore, the preparation method of this invention is simple, efficient, low-cost, and environmentally friendly, suitable for mass production, and yields gradient glass with a good gradient effect and natural transition areas.

[0079] The preferred embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0080] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0081] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A method for preparing anti-glare gradient glass, characterized in that, The method includes: S1. The surface of the glass body is subjected to a first sandblasting treatment using hard sand to obtain a first glass body; S2. The first glass body is subjected to a second sandblasting treatment using coated sand to obtain a second glass body; The first sandblasting treatment is full-surface sandblasting; the second sandblasting treatment is gradient sandblasting. The anti-glare gradient glass includes a glass body, which has a first surface. The haze difference between any two points 3 mm apart on the first surface is in the range of 0.01-5%. The maximum haze on the first surface is any value between 70-90%, and the minimum haze on the first surface is any value between 5-15%. The light transmittance at any position on the first surface is greater than 85%; The maximum surface roughness Ra on the first surface is 1.6-2.0 μm, and the minimum surface roughness Ra on the first surface is 0.1-0.5 μm.

2. The method according to claim 1, wherein, The haze difference between any two points 3 mm apart on the first surface is in the range of 0.1-1.5%.

3. The method according to claim 1, wherein, The first sandblasting process includes: controlling the spray gun to continuously spray the hard sand or a first spray material containing the hard sand and water from one end of the glass body to the other end of the glass body at a constant first predetermined speed and a first predetermined spraying distance to form the first glass body.

4. The method according to claim 3, wherein, The first predetermined speed is 1-100 mm / s, the first predetermined spray distance is 40-600 mm, and the particle size of the hard sand is 100 mesh-1000 mesh.

5. The method according to claim 1, wherein, The second sandblasting process includes: the spraying direction of the spray gun is set at an angle relative to the plane where the first glass body is located, and the spray gun is controlled to continuously spray the coated sand or a second spray material containing the coated sand and water from one end of the first glass body to the other end of the first glass body according to a second predetermined spraying distance and a gradually changing second predetermined speed, so as to form the second glass body.

6. The method according to claim 5, wherein, The second predetermined spraying distance is 100-600mm, and the angle between the spraying direction of the spray gun and the plane where the first glass body is located is 15-90°; the pressure of spraying the coated sand is 0.1-0.8MPa; The second predetermined speed is adjusted to a gradually changing second predetermined speed by gradually increasing or decreasing the moving speed of the spray gun; the gradually increasing or decreasing moving speed of the spray gun is 1-100 mm / s.

7. The method according to claim 1, wherein, The coated sand comprises hard particles and a polymer film wrapped around the hard particles; the hard particles are at least one of white fused alumina, brown fused alumina, iron sand, diamond and zircon sand; the polymer film is at least one of polyurethane film, epoxy resin film and phenolic resin film; the weight ratio between the hard particles and the polymer film is 0.5-1.5:

1.

8. The method according to claim 1, wherein, The method further includes: subjecting the second glass body to alkaline etching treatment; the alkaline substance used in the alkaline etching treatment is at least one of sodium hydroxide and potassium hydroxide, the concentration of the alkaline substance is 30-50%, the temperature of the alkaline etching is 110-140℃, and the etching time is 40-60 min.

9. An electronic device, characterized in that, The electronic device comprises gradient glass prepared by the method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Machining method for ground glass with gradual changing effect

    CN107009275A

  • Gradient glass preparation method, gradient glass and electronic equipment

    CN112679103A

  • Abrasive composition for sandblast, sandblasting method using the abrasive composition for sandblast, patterning of low-melting glass using the sandblasting method, and recycling of low-melting glass in the patterning of low- melting glass

    JP2000204354A